Management control practices as performance facilitators in a crisis context - Adelaide Martins; Cidália Oliveira; Rui Silva; Manuel Castelo Branco (Administrative Sciences, 2023)
In modern times, disruptive contexts have challenged the functioning of organisations, as shown by recent events, such as the COVID-19 pandemic and the current war in Europe. The literature highlights the role of management control practices (MCP) as resources that help to improve decision-making processes and organisational performance and competitiveness in a crisis context. In response to stakeholders' pressures, companies are integrating Corporate Social Responsibility (CSR) issues into their measurement and control systems. The aim of this research is to examine whether companies perceive MCP as a resource to support the decision-making process and contribute to organisational performance and competitiveness in a crisis environment, as well as to ascertain the perceived role of CSR in MC. A survey by questionnaire was conducted among the 250 major exporting companies in Portugal. Results show that in a crisis context of uncertainty and unpredictability such as the COVID-19 pandemic organisations perceive MCP as having (1) a significant influence on organisational performance and on leveraging organisational competitiveness; (2) a significant link with CSR. In general terms, this study provides new insights into the perceptions of the role of MCP as a valuable resource to achieve organisational competitiveness and performance in disruptive social and economic contexts.
Keywords: 350; corporate social responsibility; crisis context; management control practices; organisational competitiveness; organisational performance